Sosialisasi Handsanytizer Otomatis Guna Mencegah Penularan Covid-19 bagi siswa-siswi TPQ Darussalam di Banyuwangi - Mustika Yasi, Ratna; Anas Muhktar; Malik Yuhanas (Fakultas Teknik, Universitas PGRI Banyuwangi, 2021)
The purpose of this Community Partnership Program (PKM) activity is to provide knowledge about the importance of maintaining personal hygiene to prevent the spread of Covid-19 which is increasingly widespread among children. Partners in the activities of TPQ Darussalam students. Stages of activity 1) Planning at this stage the activities carried out are, observation, writing proposals, preparation of socialization materials, preparation of making automatic hand sanitizer tools, debriefing materials, 2) Implementation and socialization. The results of this activity are 1) socialization of automatic hand sanitizers can prevent the transmission of Covid -19 and increase public understanding and knowledge, especially students of TPQ Darussalam, Purwoharjo. 2) the availability of automatic hand sanitizer products in the students of TPQ Darussalam, Purwoharjo. Socialization activities for the use of automatic hand sanitizers and socialization to prevent the transmission of Covid-19 need to be carried out regularly.